The Role and Importance of the Nutritional Factor in Maintaining and Strengthening the Health of Children and Adolescents - Kurbanova Hurliman Amangeldievna (Scholars Digest Publishing, 2023)
This article is devoted to topical aspects of healthy nutrition of children and adolescents. The article highlights the main problems of children's nutrition, which play an essential role in maintaining and strengthening the health of children and adolescents. Among the many diverse factors that constantly affect the growing body and its health, nutrition plays an important role. Nutrition affects the further development of the child and his state of health not only at school age, but also in adulthood.
Keywords: healthy nutrition, social factors, prevention, healthy lifestyle, diseases.